Social cohesion and self-governance arrangements among small-scale fisheries in Puerto Rico - Gómez-Andújar, Nicolás X.; Gerkey, Drew; Conway, Flaxen; Watson, James R. (Frontiers in Marine Science, 2022)
In small-scale fisheries that suffer from weak formal governance, fishers use a variety of institutional strategies to self-govern. These self-governance arrangements may or may not be forms of collective action, yet they rely on informal institutions (such as norms of reciprocity) in generating social cohesion among users so that common rules can be agreed upon. Social network perspectives have been used to understand the cohesiveness of fishers operating with different gear types or in different communities, yet less is known about how social cohesion differs between fishers that operate through formal cooperative arrangements, such as fishing associations, and independent fishers who operate solely at the community level through informal cooperation. Using mixed methods, we compared the social cohesion of commercial fishers arising from information-sharing and work-support networks in four fishing communities of north-eastern Puerto Rico, as they coped with prolonged hurricane recovery and the COVID-19 pandemic. A series of exponential random graph models (ERGMs) were applied to untangle the drivers of cohesion emerging from fisher’s information-sharing patterns. Fisher’s communication was driven not just by operating at the same landing site or using the same primary gear type, but also by choosing to organize their fishing under the same self-governance arrangement. Specifically, fishers that were members of fishing associations mostly communicated among themselves, while independent fishers talked across arrangements, indicating the role of fishing associations in fostering social cohesion. However, associated fishers were less likely to receive information than independent fishers, suggesting the need for targeted communication strategies within each group. Moreover, independent fishers had more work support ties and a greater diversity of supporting actors across the supply chain, suggesting their need for higher levels of linking social capital. Multiple social factors explained whether fishers choose to be members of fishing associations or remain independent, including trust in leaders and agreement on membership rules. These findings highlight the importance of knowing the cohesiveness of cooperation networks among small-scale fishers.